(untitled) (Scientia Agropecuaria, 2021)
This study was embarked on to unveil the impact of COVID-19-induced migration on agricultural productivity in Delta State, Nigeria. This survey study involved rural arable crop farmers. Data were collected from households and community survey of 517 families through structured interview schedule (questionnaire administered by face to face interview). It was found that 41% and 30% of the present and second generations respectively, in receiving communities were immigrants. In receiving communities, 68% of the households were of the largest ethnic group compared to 95% fraction in sending communities. Households in sending communities had smaller farm sizes than those in receiving communities. In sending communities, 41% and 65% of the migrant and indigenous populations, respectively, contacted the disease, while there was no recorded case in receiving communities. The mean yield in receiving communities was higher than that in the sending communities. COVID-19 incidents and other factors influenced immigration to receiving communities. The soil and land factors in receiving communities also contributed to decision on migration. Migration increased agricultural productivity in receiving communities, while productivity was reduced in sending communities. However, other factors such as distance to farm, farm size, age of household head and assets also affected yields in sending and receiving communities. The policy implications are that government ought to have considered the fact that, naturally, farm families work while giving distances to themselves in farms. Communities need to participate in decisions on issues like this in the future to collectively, fathom a way out especially in rural communities.